Immune activation attenuates memory acquisition and consolidation of conditioned disgust (anticipatory nausea) in rats - Bishnoi, Indra R.; Kavaliers, Martin; Ossenkopp, Klaus-Peter (Behavioural brain research, 2023)
Anticipatory nausea is a classically conditioned response to cues (e.g. contexts) that have been previously paired with a nauseating stimulus, such as chemotherapy in humans. In rodents, anticipatory nausea can be modeled by pairing a novel context with lithium chloride (LiCl), which leads to conditioned disgust behaviours (such as gaping) when exposed to the context alone. Growing evidence suggests that selective immune activation attenuates various forms of learning and memory. The present study investigated the effects of the endotoxin lipopolysaccharide (LPS) on LiCl-induced anticipatory nausea across critical stages of associative memory including acquisition, consolidation, and extinction. Adult male Long Evans rats were subject to intraperitoneal (i.p.) LiCl (127 mg/kg) or vehicle control (NaCl) paired with a 30 min conditioning trial in a distinct context for a total of 4 trials. To study acquisition, rats were administered either LPS or NaCl (200 μg/kg, i.p.) 90 mins before the conditioning trials. To study consolidation, different rats were administered either LPS or NaCl (200 μg/kg, i.p.) immediately after the conditioning trials. These trials were followed by 4 drug-free extinction trials within the same context. LPS significantly reduced conditioned gaping behaviours by the 4th conditioning trial and on the 1st drug-free extinction trial when administered 90 mins before or immediately after the conditioning trials. LPS had no significant effect on extinction. The present study provides strong evidence for the attenuating effects of LPS exposure on the acquisition and consolidation of LiCl-induced anticipatory nausea. •Lithium chloride can be used to model anticipatory nausea in rodents.•Lipopolysaccharide prevents anticipatory nausea acquisition.•Lipopolysaccharide impairs anticipatory nausea consolidation.•Lipopolysaccharide has no effect on the extinction of anticipatory nausea.•Immune stimulation can disrupt the learning and memory of conditioned disgust.